Застосування геофізичних технологій при вирішенні різноманітних завдань техногенної безпеки - Пігулевський, П.Г.; Свистун, В.К.; Пахомов, С.П.; Тяпкін, О.К.; Кирилюк, О.С. (Геоінформатика, 2015)
Проаналізовано можливості ефективного використання геофізичних методів за комплексного вивчення впливу техносфери на геологічне середовище для вирішення завдань техногенної безпеки. Як приклад розглянуто результати виконання робіт геоелектричними методами Дніпропетровською геофізичною експедицією “Дніпрогеофізика” під час картування масивів гірських порід для виявлення пустот і місць можливого воронкоутворення на полігоні складування відходів будівельних матеріалів коксохімічного заводу. Для вирішення поставлених завдань використано комплекс геофізичних методів, який включав аудіомагнітотелуричне зондування і резонансно-акустичне профілювання. Викладено можливості геоелектричних методів під час пошуку підземних пустот у масивах гірських порід та оцінювання процесів воронкоутворення, описано методику виконання польових робіт, результати обробки й гірничо-геологічної інтерпретації даних цих методів. Установлено, що гірські пустоти інтенсивно впливають на стан досліджуваних масивів і розвиток “неотектонічних” процесів та зміну гідродинамічного режиму як підземних, так і ґрунтових вод, що призводить до інтенсивної диференціації фізико-механічних властивостей середовища й утворення ослаблених зон, де можливе осідання поверхні. Анализируются возможности эффективного применения комплекса геофизических методов при изучении влияния техносферы на геологическую среду и решении задач техногенной безопасности. В качестве примера рассмотрены результаты выполнения работ геоэлектрическими методами Днепропетровской геофизической экспедицией “Днепрогеофизика” при картировании массивов горных пород с целью выявления пустот и мест возможного воронкообразования на полигоне складирования отходов строительных материалов коксохимического завода. Для решения поставленных задач использовался комплекс геофизических методов, который включал аудимагнитотеллурическое зондирование и резонансно-акустическое профилирование. Изложены возможности геоэлектрических методов при оценке процессов воронкообразования и поиске подземных пустот в массивах горных пород, описаны методика выполнения полевых работ, результаты обработки и горно-геологической интерпретации данных этих методов. Установлено, что горные выработки интенсивно воздействуют на состояние изучаемых массивов пространства, на развитие “неотектонических” процессов, изменение гидродинамического режима как подземных, так и грунтовых вод. Эти изменения вызывают интенсивную дифференциацию физико-механических свойств среды и образование ослабленных зон, в которых может произойти просадка поверхности. Purpose. The purpose of the paper is to investigate the possibility of effective application of geophysical methods for detection and mapping in the areas of active mining of mineral deposits (with open-pit or mining methods), sites of common natural and man-made cavities and areas of possible formation of craters; to carry out experimental geophysical investigations on the territory of the Kryvyi Rih iron ore basin.
Design/methodology/approach. Experimental studies were carried out using audio-magneto-telluric sounding (AMTS) and resonance-acoustic profiling (RAP). AMTS works were done in the frequency range from 1 to 10 000 Gts with station MTU-5A Canadian company “Phoenix” on the profiles located above the estimated cavities and weak intervals (fractured zones). Five components of the electromagnetic field (Ex, Ey, Hx, Hy, Hz) were recorded. The duration of a single-recording was 15 minutes. The RAP measurements were carried out by a hardware complex RAP-2008 at a sampling rate of 2000 Hz signal, the length of the recorded signal being 8,192 responses.
Findings. Anomalous zones associated with the presence of man-made cavities represented as long abandoned mine workings were discovered and mapped within the surveyed area on the landfill of waste disposal of building materials at the Kryvyi Rih Coke Plant. The places of potential craters above them were detected. Identification of the areas of possible crater formation was carried out with low resistance (1—10 Ohm*m) using AMTS method, and with morphology of the areas of high gradients of the frequency spectra for RAP-sections. Detection of prospective areas of underground cavities and the resulting decompressed zones was conducted with a high resistance of 200 to 1000 Ohmm using AMTS method and with structural characteristics of the frequency spectrum and amplitude (RAP method). The results show that the mine workings had an intense impact on the environment, triggering “neotectonic” processes and changing the hydrodynamic conditions of the underground and ground water. These changes caused an intense differentiation of physical-mechanical properties of the geological environment and zones formation, weakness leading to drawdown in the projections to their surface.
Practical value/implications. The proposed technology permits to quickly detect and map the areas of crater formation and underground cavities of natural and anthropogenic origin within urban agglomerations. Recommendations should be given to urban development organizations on developing the area over exhaust underground workings and near large open pits.